Strategi Guru Dalam Meningkatkan Keaktifan Belajar Siswa Pada Mata Pelajaran PAI di SMA Muhammadiyah Gunung Meriah Aceh Singkil - Desriadi Desriadi (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2017)
In order to improve students' learning activeness in SMA Muhammadiyah, the necessary strategies of teachers in particular here is the Islamic religion teachers. Because high school students still need guidance in learning Islam. SMA Muhammadiyah is one high school in the district of Gunung Meriah which has the goal of keeping students who are Muslims capable of Islamic studies. While in reality the portion hours of learning Islam 2 hours per week. Therefore, researchers wanted to try to express how strategies to enhance the activity of Islamic religion in Islamic studies in SMA Muhammadiyah. The purpose of this study is to describe forms of Islamic religious teachers strategies to improve the activity of Islamic studies student at SMA Muhammadiyah with all efforts, obstacles and measures to solve the Islamic religion teachers in improving student learning activeness Islamic religion. To obtain the data in this study the authors used the instrument of observation, documentation and questionnaires.